The Upper Adriatic Trans-European Transport Network along the Trieste-Koper Axis - Salvatore Polverino (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
This paper-Review aims to clarify the infrastructural development of the Adriatic-Ionian macro-region and its difficult cross-border vision towards the Trans European Transport Network (TEN-T). Two Port Authorities competitors, Trieste and Koper have aimed to build a secondary track system to fulfill the EU sustainability and to adhere to the silk-road model. Trieste takes advantage of Annex VI, part of the Treaty of Paris, that has guaranteed a Free Port legal regime in combination with the recent Special Economic Zone (ZES), by which a further tax relief has played a strong Key-enabler role. With the analysis of Geographic Information System, Open License Database and evaluation methods have been compared and visualized to highlight the mismatch of their Cross-border cooperation. The expressed results lead to feasibility-costs' overviews and EU finance strategies in which is highlighted the competition between the two Port Authorities, and their final horizontal (re)integration of borders.